2017
DOI: 10.25271/2017.5.1.314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Occupational Noise Exposure on Blood Pressure and other Aspects of Health for Workers in Selected Industrial Places in Zakho City, Iraq

Abstract: Industrial or Occupational noise play a vital role in the life of workers. This source of pollution disrupts and annoys the daily activities of workers. Occupational Noise pollution is increasingly being recognized as a physical factor in the environment that is injurious to many aspects of health. This study focuses on the industrial noise and its effects on workers. The aim of the study is to find out the possible relation between the occupational noise exposure and arterial blood pressure, pulse rate, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…But the statutory activation is incomplete or ignored or completely unknown. Therefore, the media should play a particular role in this issue (Yousif and Mahdi, 2013). A survey of 90 workers from various businesses in Duhok indicated that noise levels in all industries are much higher than the maximum (OSHA) exposure restrictions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But the statutory activation is incomplete or ignored or completely unknown. Therefore, the media should play a particular role in this issue (Yousif and Mahdi, 2013). A survey of 90 workers from various businesses in Duhok indicated that noise levels in all industries are much higher than the maximum (OSHA) exposure restrictions.…”
Section: Resultsmentioning
confidence: 99%
“…The sources of annoying voice in Iraq are numerous, and that may be resulted from using the old vehicle or using enormous numbers of generators, or it may be caused by industrial machinery and processes such as electrical machinery and process such as drilling, carpentry, pneumatic tool, crushing, pumps and compressors, etc. (Yousif and Mahdi, 2013). The main study objectives were to assess the health and environmental safety levels in food and water production factories and measure noise levels.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational noise exposure to workers have adverse effects on workers' health by increasing hypertension, sleep disturbance [81], cardiovascular diseases, blood pressure, hypertension [82,83], exhaustion and overworking, mistakes performed in various operations due to noise disturbance [84], memory impairment [85], increased pulse rate [86], hearing loss and diabetes [87,88].…”
Section: On Industrial Workersmentioning
confidence: 99%
“…The term "noise pollution" was coined to signify the vast cacophony of sounds that are produced as a consequence of modern life, leading to certain associated health hazards [1]. The term noise is commonly used to describe "unwanted sound", or sounds that are unpleasant or disagreeable and produced by acoustic waves of random intensities and frequencies [2,3]. When people are exposed to excessive amounts of sound waves, their health can be put at risk [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sounds exceeding 70 dB are considered harmful to human health, and it is advisable not to be exposed to such noises [15]. According to the "Occupational Safety and Health Administration (OSHA)" in the U.S.A, exposure for more than 8 hours a day to sound over 85 dB is highly risky and is used as a warning limit, whilst the sound levels of 90 dB or greater are considered dangerous on exposure for more than eight hours per day [2,14]. Nowadays, noise pollution is the third-most hazardous environmental type of pollution according to the "World Health Organization (WHO)" and is preceded only by air and water pollution [16,17,18].…”
Section: Introductionmentioning
confidence: 99%